A multicenter, phase II study of maintenance azacitidine in older patients with acute myeloid leukemia in complete remission after induction chemotherapy. Issue 9 (14th August 2015) - Griffin, Patrick T.; Komrokji, Rami S.; De Castro, Carlos M.; Rizzieri, David A.; Melchert, Magda; List, Alan F.; Lancet, Jeffrey E.
<x xml:space="preserve">Abstract</x> Older patients with acute myeloid leukemia (AML) have poor outcomes, with median durations of complete remission lasting less than 1 year. Increased toxicity in older patients limits the delivery of standard consolidation therapies, such as allogeneic stem cell transplant or high‐dose cytarabine. Azacitidine, a nucleoside analog/DNA methyltransferase inhibitor, has demonstrated significant activity and favorable tolerability in patients unable to tolerate intensive induction chemotherapy; however, the role of azacitidine in the maintenance setting has not been fully evaluated. We undertook a pilot study of low‐dose subcutaneous azacitidine [50 mg/(m2 day)] for 5 days every 4 weeks) in AML patients ≥60 years of age in first remission following standard induction therapy. The primary objective was to determine the 1‐year disease‐free survival (DFS); secondary objectives were to determine safety and tolerability. We enrolled 24 patients (median age 68, range 62–81 years), the majority of whom received anthracycline‐cytarabine induction regimens. From the time of first complete remission, the estimated 1‐year DFS was 50% and the median overall survival was 20.4 months. Thrombocytopenia and neutropenia were the most common grade 3/4 toxicities (50 and 58%, respectively). In our study population, maintenance therapy with subcutaneous azacitidine was safe and well tolerated. Am. J. Hematol. 90:796–799, 2015. © 2015 Wiley Periodicals, Inc.